Selecting better attributes in third-party hotel reservation Web sites: A comparative analysis - Huertas, Ruben; Casas, Agusti; Subira, Esther (UI Scholars Hub, 2021)
Internet has been viewed by many travel organizations as an innovative and competitive marketing tool in offering travel-related information and online transaction opportunities (Doolin et al., 2002). But, Internet also has proportionate opportunities to appear new intermediaries in the new hotel value chain (Connolly et al., 1998). A substantial portion of online room reservations continues to be accounted by the third-party Web sites (Law and Cheung, 2006). Hotels have been actively involved in multi-channel distribution in order to sell products and services more efficiently using a combination of traditional and electronic channels. It is important for organizations to rely on the channels that best match the organizational goals (O’Connor and Frew, 2004).The methodology for the experiment follows Statistical Design of Experiments (SDE). SDE is a statistical technique useful for developing, improving and optimizing processes and also has important applications in research into customer psychology and behaviour (Rosenbaum 1999). However, SDE is not a new tool in marketing; pioneering works such as those by Holland and Cravens (1973), Chevalier (1975) and more recently those of Starkey, Aughton and Brewin (1997), Almquist y Wyner (2001) have used full factorials and fractional factorial designs. In this work we use a fractional factorial design in four four-size blocks design and we have not find any reference that use this kind of design in Marketing.